Incorporating Heuristic Evaluation (HE) in the Evaluation of Visual Design of the Eco-Tourism Smartphone App - Tanalachimi Ganapathy; mohd kamal othman; AbdulRazak Saleh Yahya (ITB Journal Publisher, LPPM ITB, 2021)
Heuristic Evaluation (HE) has proven to be important in the development of different computer systems but has not been incorporated in the development of eco-tourism smartphone applications. This results inusability issues that significantly affect user experience (UX) as discussed in literature. This study reports the HE in the design and development of Niranur Agro Farm (NAF) eco-tourism smartphone applications, which could improve UX. Eight experts participated in this study, utilizing the SMART mobile usability heuristic developed for mobile application and the severity rating scale to determine usability issues. The HE findings indicated that 22 usability issues were identified. One issue was rated 4 (catastrophe), four issues were rated 3 (major problem), twelve issues were rated 2 (minor problem) and five issues were rated 1 (cosmetics). Although there are issues rated as 4 and 3, the majority of the issues were considered to be minor (1 and 2 on the scale). Results indicated that it is crucial to incorporate HE into the design and development of the eco-tourism smartphone app to minimize the usability issues faced by users. It further validated that utilizing a specific heuristic for smartphone applications would ensure that all usability issues are correctly categorized and remedied.